2018
DOI: 10.4314/ijbcs.v11i5.22
|View full text |Cite
|
Sign up to set email alerts
|

Comment les aires protégées structurent les écosystèmes des périphéries

Abstract: RESUMECette étude menée a pour but de montrer l'influence des aires protégées sur la structuration des écosystèmes périphériques. Pour cela, une étude diachronique par images satellitaires Landsat de 1985 à 2013 a été faite et une collecte de données de terrain a été réalisée dans les villages autour du Parc National de Manda dans le méridien tchadien en vue d'apprécier la gestion de la biodiversité de leur entourage. Des résultats, il ressort que la création du parc a favorisé la délocalisation de certains vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
7
0
0
Order By: Relevance
“…consisting of croplands and fallows which in 2013 occupy respectively 40% and 28% of the total surface area. These results are similar to those found by Avakoudjo et al (2014) and Benoudjita & Djinet (2017) Deforestation and degradation of FCDK is clearly perceptible between 1972 and 1999. This brutal land cover change is a result of migration to the south of the country of civil servants who fled the civil war in years 1970 and converted into farmers and breeders.…”
Section: Searchsupporting
confidence: 90%
See 1 more Smart Citation
“…consisting of croplands and fallows which in 2013 occupy respectively 40% and 28% of the total surface area. These results are similar to those found by Avakoudjo et al (2014) and Benoudjita & Djinet (2017) Deforestation and degradation of FCDK is clearly perceptible between 1972 and 1999. This brutal land cover change is a result of migration to the south of the country of civil servants who fled the civil war in years 1970 and converted into farmers and breeders.…”
Section: Searchsupporting
confidence: 90%
“…Indeed from 1955 the year of classification until 2008, no effective protection measures were taken to conserve the resources of this forest. Similar drivers of degradation have also been observed by Saradoum (2012), Avakoudjo et al (2014) and Benoudjita & Djinet (2017) in Chad and in other West African countries. In Cameroon, Wafo et al (2006) and Momo et al (2018) have found same degradation trends and similar drivers respectively for the Madjam forest reserve in the far north and the Koupa-Matapit gallery forest in the West.…”
Section: Searchsupporting
confidence: 80%
“…The clear forest particularly recorded a decrease of more than 50% of its surface. These results are similar to those of Temgoua et al (2018b) in the classified forest of Djio-li-Kera in southeast Chad and those of Benoudjita & Ignassou (2017) in and around the W Regional Park of Benin, which showed a continuous regression in forest and savannah at the expense of fallows, crop fields, bare soil and settlements. The search for new arable land to feed a population in perpetual growth could justify the increase over the years of anthropogenic spaces.…”
Section: Dynamics Of Vegetation Cover and Explanatory Factorssupporting
confidence: 85%
“…The same result were obtained by (Djiongo et al, 2020) in the Bouba Ndjidda National Park who reported a regression in natural plant formations by 13.4% in 26 years at the expense of anthropogenic activities such as crop fields, bare soil, and infrastructure. These results are also similar to those of (Temgoua et al, 2018b) in the classified forest of Djio-li-Kera in southeast Chad and those (Benoudjita & Ignassou, 2017) in and around the W Regional Park of Benin, which shows a continuous regression in forest and savannah at the expense of fallows, crop fields, bare soil and settlements. Report by (Temgoua et al, 2018a) progressively.…”
Section: Dynamics Of Land Use/land Cover Changesupporting
confidence: 86%